Islamic Values in The Kompangan Performance Tradition of The Jambi Malay Community - Gusriyeni, Gusriyeni; Yahya, Vivi Aleyda; Fatika, Muhammad Riski; Saputra, Muhammad Adi; Waluyo, Hadi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The Jambi Malay community's kompangan tradition integrates Islamic values ​​into percussion music that accompanies traditional and religious events, but in-depth studies on the internalization of these teachings are still limited. This study aims to examine Islamic values ​​such as monotheism, propagation, and brotherhood in kompangan performances. Using a qualitative-descriptive approach with a literature study method, the population includes written sources about kompangan (2018-2025), while a purposive sample includes 25-30 relevant documents from Google Scholar. The main instruments are journal and book documents, analyzed through reduction, presentation, and thematic interpretation with triangulation. The results show that kompangan is full of the values ​​of monotheism through shalawat poetry, ukhuwah from group togetherness, Islamic aesthetics, morals, and spiritual dhikr. The conclusion states that kompangan is an effective cultural da'wah medium that strengthens the religious identity of the Jambi Malay, recommended for educational preservation.